Headache and neck or shoulderpain. An analysis of musculoskeletal problems in three comprehensive population studies in Northern Norway. - Hasvold, Toralf (Universitetet i Tromsø, 1992)
Papers in this thesis: I: B. K. Jacobsena1 c1, T. Hasvolda1, G. Høyera1 and V. Hansen: ‘The General Health Questionnaire: how many items are really necessary in population surveys?’. Psychological Medicine, Volume 25, Issue 05, September 1995, pp 957-961 ( http://dx.doi.org/10.1017/S0033291700037442 ) II: Toralf Hasvold, and Roar Johnsen: ‘Headache and neck or shoulder pain - frequent and disabling complaints in the general population’. Scandinavian Journal of Primary Health Care, 1993, Vol. 11, No. 3, Pages 219-224. III: Toralf Hasvold and Roar Johnsen: ‘Headache and neck or shoulder pain—family learnt illnesses behaviour? The Bardu Muscoloskeletal Study, 1989–1990’. Family Practice (1996) 13 (3): 242-246 ( http://dx.doi.org/10.1093/fampra/13.3.242 ) IV: Toralf Hasvold, Roar Johnsen, Olav Helge Førde: ‘Non-migrainous headache, neck or shoulder pain, and migraine — differences in association with background factors in a city population’. Scandinavian Journal of Primary Health Care Jan 1996, Vol. 14, No. 2: 92–99. V: Toralf Hasvold, Roar Johnsen, Olav Helge Førde: ‘Musculoskeletal problems- result of “mental pain” rather than physical strain?. (Manuscript).